CREED study: Hypoglycaemia during Ramadan in individuals with Type 2 diabetes mellitus from three continents. (October 2017) - Jabbar, Abdul; Hassanein, Mohamed; Beshyah, Salem A.; Boye, Kristina S.; Yu, Maria; Babineaux, Steven M.
Highlights: Incidence of hypoglycaemia during Ramadan ranged from 4.1 to 13% across the regions. Incidence of hypoglycaemia was higher when insulin was used. Prior hypoglycaemia greatly increased the likelihood of an episode during Ramadan. Abstract: Aims: To describe diabetes treatment and hypoglycaemia in individuals with Type 2 diabetes mellitus during Ramadan. Methods: A multi-country, retrospective, observational study with data captured before, during, and after Ramadan. We report on a cohort of people ( N = 3250) with Type 2 diabetes mellitus in four culturally distinct regions: Asia, North Africa, Europe, and the Middle East. Results: During Ramadan, the proportion of participants on oral anti-diabetic medication alone ranged from 68.4% (Middle East) to 80.5% (Asia); the proportion on insulin alone ranged from 3.7% (Middle East) to 8.6% (Europe). The average number of days fasted for individuals with an American Diabetes Association (ADA) risk status of very high was 27 (Middle East), 25.7 (Asia), 25.4 (North Africa), and 21 (Europe). The incidence of hypoglycaemia according to an ADA risk status of very high was 5.6% ( n = 1/18, Europe), 6.1% ( n = 2/33, Middle East), 8.7% ( n = 4/46, Asia), and 38% ( n = 10/26, North Africa). The incidence of hypoglycaemia, during Ramadan, for the entire cohort was 16.8% with insulin treatment and 5.3% with oral anti-diabetic medication. Having an episode of hypoglycaemia before Ramadan was associated with hypoglycaemia during Ramadan (odds ratio 7.80; 95% confidence interval 5.31–11.45). Conclusions: Approaches to the management of Type 2 diabetes mellitus during Ramadan varied across regions. Episodes of hypoglycaemia and insulin therapy predicted risk of hypoglycaemia during Ramadan and identified individuals who required Ramadan-specific education.